2018
DOI: 10.15448/1980-6108.2018.4.32395
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to learning and academic performance in pharmacology among second-year undergraduate medical students

Abstract: AIMS: To determine the learning approach of second-year undergraduate medical students and whether a surface or deep approach to learning had any correlation with the pharmacology sessional and university examination marks obtained.METHODS: A cross-sectional study was conducted among second-year medical students in their fifth semester. To determine the students’ learning approach, whether superficial or deep, we used the Revised Two Factor Study Process Questionnaire (R-SPQ-2F), which contains 20 items in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
2
5
0
1
Order By: Relevance
“…This pattern is consistent with findings from heterogeneous student samples in Turkey and Taiwan (males higher on deep learning) [41], and among math students in Vietnam (females higher on strategic learning) [18]. However, we were not able to demonstrate significant associations between gender and students' approach to study, in line with previously reported studies involving psychology students [45,46], medical students [17,47] and science students [48]. In general, it is complicated to explain phenomena that are formed and developed on the basis of interactions between and combinations of inherent and acquired factors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This pattern is consistent with findings from heterogeneous student samples in Turkey and Taiwan (males higher on deep learning) [41], and among math students in Vietnam (females higher on strategic learning) [18]. However, we were not able to demonstrate significant associations between gender and students' approach to study, in line with previously reported studies involving psychology students [45,46], medical students [17,47] and science students [48]. In general, it is complicated to explain phenomena that are formed and developed on the basis of interactions between and combinations of inherent and acquired factors.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, higher academic achievements have been associated with a strategic study approach [12,15]. Conversely, a surface approach to studying has been linked to several detrimental outcomes, such as lower academic achievement [12,[15][16][17][18][19], increased risk of dropping out of academic study programs [20], Dominant approaches to studying 4 lower academic expectations [7], increased test anxiety [21], and higher levels of stress [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have further shown that learning approaches of the students did not differ by gender. This is similar to the findings of Hussin et al (2017) who used a sample of engineering students and also to Kamath et al (2018) using a sample of medical students. This is, however, contrary to the report of Arsaythamby et al (2015) in a study carried out on a sample of English undergraduate students.…”
Section: Discussionsupporting
confidence: 90%
“…The findings revealed that engineering students predominantly use deep learning approach. Kamath et al (2018) also investigated the learning approaches of second year medical students and the findings also revealed that the students adopted a deep learning approach. Arsaythamby et al (2015), on the contrary, reported a predominant use of surface learning approaches by English undergraduate students among University Utara, Malaysia.…”
Section: Student Learning Approach and Academic Performancementioning
confidence: 99%